Coaches` perceptions of team cohesion in paralympic sports - Falcão, W. R.; Bloom, G. A.; Loughead, T. M. (Adapted Physical Activity Quarterly, 2015)
The purpose of this study was to investigate Paralympic coaches` perceptions of team cohesion. Seven head coaches of summer and winter Canadian Paralympic sport teams participated in the study. Four participants coached individual sports and 3 coached team sports. Data were collected using semistructured interviews and analyzed using thematic analysis. The results addressed the coaches` perceptions of cohesion in the Paralympic sport setting and strategies used to foster cohesion with their teams. Participants described using techniques and strategies for enhancing cohesion that were similar to those in nondisability sport, such as task-related activities, goal setting, and regularly communicating with their athletes. They also listed how cohesion was distinct to the Paralympic setting, such as the importance of interpersonal activities to build social cohesion. The implications of these results for coaching athletes with a disability are also presented.